Correction: ensemble models of neutrophil trafficking in severe sepsis. - Sang Ok Song; Justin Hogg; Zhi-Yong Peng; Robert Parker; John A Kellum; Gilles Clermont (PLoS Computational Biology)
[This corrects the article on p. e1002422 in vol. 8.].